Impact of bladder, bowel and sexual dysfunction on health status of people with thoracolumbar spinal cord injuries living in the community. (3rd September 2017) - Park, So Eyun; Elliott, Stacy; Noonan, Vanessa K.; Thorogood, Nancy P.; Fallah, Nader; Aludino, Allan; Dvorak, Marcel F.
Abstract : Objective . The disruption of autonomic function following a spinal cord injury (SCI) is common and can negatively affect quality of life. The objective of this study was to describe the prevalence of bladder/bowel incontinence and sexual dysfunction in community-dwelling individuals with a thoracolumbar SCI and examine the impact on general physical and mental health status. Methods . Participants who sustained a traumatic SCI to the thoracolumbar region of the spinal cord and classified as American Spinal Injury Association Impairment Scale (AIS) A to D were recruited. Demographic, injury data, MRI classification and neurological data were collected on admission. At follow-up, the neurological data, a questionnaire collecting participant-reported secondary health conditions (SHCs) (e.g. bladder incontinence, depression etc.) following SCI and health status measured by Short Form-36 were obtained. Regression models determined the association of health status with demographic/injury-related data, types and number of SHCs. Results . Of the 51 participants, 58.8% reported bladder incontinence, 54.0% bowel incontinence, 60.8% sexual dysfunction and 29.4% had all three. The regression models demonstrated that age at injury, bowel incontinence, sexual dysfunction, presence of pain, motor score at follow-up and the number of SHCs were significant predictors of health status. The number of SHCs was more predictive than all other demographic and injury variables for health status. Conclusion . Results highlight the high prevalence of self-reported bowel/bladder incontinence and sexual dysfunction in the traumatic thoracolumbar SCI population and support the need for standardized assessments. Several demographic, injury-related and SHCs impacted health status and should be considered for the management of individuals living in the community.